Factors influencing the preference for purchasing generic drugs in a Southern Brazilian city - Marília Cruz Guttier; Marysabel Pinto Telis Silveira; Vera Lucia Luiza; Andréa Dâmaso Bertoldi
ABSTRACT OBJECTIVE The objective of this study is to identify factors associated with the preference for purchasing generic drugs in a medium-sized municipality in Southern Brazil. METHODS We have analyzed data from a population-based cross-sectional study conducted in 2012 with a sample of 2,856 adults (≥ 20 years old). The preference for purchasing generic drugs was the main outcome. The explanatory variables were the demographic and socioeconomic variables. Statistical analyses included Poisson regressions. RESULTS The preference for purchasing generic drugs was 63.2% (95%CI 61.4-64.9). The variables correlated with this preference in the fully adjusted models were: male (prevalence ratio [PR] = 1.08; 95%CI 1.03-1.14), age of 20-39 years (PR = 1.10; 95%CI 1.02-1.20), low socioeconomic status (PR = 1.15; 95%CI 1.03-1.28), and good knowledge about generic drugs (PR= 4.66; 95%CI 2.89-7.52). Among those who preferred to purchase generic drugs, 55.1% have reported accepting to replace the prescribed drug (if not a generic) with the equivalent generic drug. Another correlate of the preference for purchasing generic drugs was because individuals consider their quality equivalent to reference medicines (PR = 2.15; 95%CI 1.93-2.41). CONCLUSIONS Knowledge about generic drugs was the main correlate of the preference for purchasing generic drugs. The greater the knowledge or positive perception about generic drugs, the greater is the preference to purchase them. Therefore, educational campaigns for healthcare professionals and consumers appear to be the best strategy for expanding the use of generic drugs in Brazil.